2020
DOI: 10.36685/phi.v6i1.318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation of F100 Biscuits Modified With Moringa Oleifera Flour Substitution on Nutritional Status of Under-Five Children With Malnutrition in Kendari City Indonesia

Abstract: Background: Malnutrition is a condition of severe nutritional deficiency caused by an insufficient intake of energy and protein from daily food consumption. The most lethal impacts are declined IQ score, decreased cognitive development, and diminished sensory integration, which could harm the life of the children and resulted in the loss of the national youth generation. One effort to overcome this problem is to develop a diet alternative using F100 materials substituted from kelor (Moringa Oleifera) flour as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Freshly picked Moringa leaves have a nutritional content of 100 grams which is equivalent to 8 grams of dried Moringa leaves which are effective in increasing the weight of children under five years who experience Caloric Energy Deficiency and malnutrition (21). This research is in line with the results of research conducted by Riska Mayangsari et al, in 2020 which found that there was a significant effect of giving 6 biscuits equivalent to 100 grams per day to improve nutritional status in toddlers who were experiencing malnutrition (22). The results of Yulia Fitri et al, 2020's research are also in line with this study which says that providing biscuits (dry snacks) with the addition of 100 mg of Moringa leaf powder per day for 3 weeks significantly increases toddler's weight (p-value = 0.000) (20).…”
Section: Discussionsupporting
confidence: 91%
“…Freshly picked Moringa leaves have a nutritional content of 100 grams which is equivalent to 8 grams of dried Moringa leaves which are effective in increasing the weight of children under five years who experience Caloric Energy Deficiency and malnutrition (21). This research is in line with the results of research conducted by Riska Mayangsari et al, in 2020 which found that there was a significant effect of giving 6 biscuits equivalent to 100 grams per day to improve nutritional status in toddlers who were experiencing malnutrition (22). The results of Yulia Fitri et al, 2020's research are also in line with this study which says that providing biscuits (dry snacks) with the addition of 100 mg of Moringa leaf powder per day for 3 weeks significantly increases toddler's weight (p-value = 0.000) (20).…”
Section: Discussionsupporting
confidence: 91%
“…To increase nutrient content and extend shelf life, fresh Moringa leaves become Moringa leaf powder 14 . According to the research results of Mayangsari R and Rasmiati K 2020, when compared to fresh Moringa leaves, the nutritional content in the form of Moringa leaves is much higher, such as carbohydrates 36.16 grams; 2.16 grams of fat; 27.75 grams of protein; in 100 grams of Moringa leaf powder 15 . According to the results of previous research, the nutritional content of Moringa leaf flour is beta-carotene content 10 times carrots, 25 times banana potassium, 25 times iron spinach, ½ times vitamin C oranges, 17 times calcium milk, and 9 times yogurt protein.…”
Section: Introductionmentioning
confidence: 98%
“…Addition of Moringa leaf powder ( MOLP ) in snacks can contribute to coping problem nutrition in children who are vulnerable to malnutrition (Zungu et al, 2020). Fortified biscuits powder leaf moringa increase heavy body child not enough nutrition (Has & Ariestiningsih, 2020;Mayangsari & Rasmiati, 2020). While research in Northern Benin observed impact gift fortified food with 15 gr of powder moringa for 2 weeks no raise heavy body child in a manner significant (Naga & Jo, 2020).…”
Section: Introductionmentioning
confidence: 99%